UKURAN DAN BENTUK LENGKUNG GIGI PADA FASE GELIGI BERCAMPUR PADA ANAK SUKU JAWA (Kajian di Kecamatan Pakem, Kabupaten Sleman, Yogyakarta) - , BERLIAN PRIHATININGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
During the period of growth and development of the teeth there is a change in the size and shape of the dental arch. Each race has a standard size and shape of the dental arch and this is not the same in every race so we need a study of standard size and shape of the dental arch to the Javanese. The purpose of this study was to obtain standard size and shape of the dental arch of the Javanese children in Pakem the district of Sleman district of Yogyakarta in the mixed dentition phase. Subjects 140 children aged 6-12 years living in the district of Sleman Pakem, divided by 7 age groups and has met the requirements of inclusion. Calculation and determination of the size of the dental arch form at molding a model study conducted by using vernier caliper and ruler based methods Raberin, et al (1993). Statistical analysis using univariate ANOVA. The results showed that the size of the dental arch width was not significantly different (p> 0.05), the size of the dental arch length significantly dif ferent (p <0.05). Dental arch form boys and girls aged 6-12 years are wide. The conclusion of this study is the increasing age the greater the size of the dental arch. The size of the dental arch tad bigger than girls. Dental arch form boys and girls is wide.